2021
DOI: 10.48550/arxiv.2101.03794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Flatband generator in two dimensions

Wulayimu Maimaiti,
Alexei Andreanov,
Sergej Flach

Abstract: Dispersionless bands -flatbands -provide an excellent testbed for novel physical phases due to the fine-tuned character of flatband tight-binding Hamiltonians. The accompanying macroscopic degeneracy makes any perturbation relevant, no matter how small. For short-range hoppings flatbands support compact localized states, which allowed to develop systematic flatband generators in d = 1 dimension in Phys. Rev. B 95 115135 (2017) and Phys. Rev. B 99 125129 (2019). Here we extend this generator approach to d = 2 d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…III D) as the unit cell of the generated lattice H . The induced CLSs then occupy U = 1 unit cell each, using the number of occupied unit cells U as a flat band classifier [27] (recently generalized accordingly for lattice dimensions d > 1 [61]). One could in principle, however, start with a supercell H of a target lattice H , consisting of U > 1 interconnected copies of H, and look for new cospectral pairs {u , v } which are not cospectral in H. Then, CLSs induced by {u , v }-odd eigenstates of H will generally occupy U > 1 primitive unit cells within the supercell.…”
Section: A Number and Spatial Extension Of Clssmentioning
confidence: 99%

Flat bands by latent symmetry

Morfonios,
Röntgen,
Pyzh
et al. 2021
Preprint
“…III D) as the unit cell of the generated lattice H . The induced CLSs then occupy U = 1 unit cell each, using the number of occupied unit cells U as a flat band classifier [27] (recently generalized accordingly for lattice dimensions d > 1 [61]). One could in principle, however, start with a supercell H of a target lattice H , consisting of U > 1 interconnected copies of H, and look for new cospectral pairs {u , v } which are not cospectral in H. Then, CLSs induced by {u , v }-odd eigenstates of H will generally occupy U > 1 primitive unit cells within the supercell.…”
Section: A Number and Spatial Extension Of Clssmentioning
confidence: 99%

Flat bands by latent symmetry

Morfonios,
Röntgen,
Pyzh
et al. 2021
Preprint
“…Such schemes make use of graph theory [6,7,[21][22][23], Origami rules [24], repeated miniarrays [25], a bipartite lattice structure [26,27], generic existence conditions [28,29], or the extension of known flat-band lattices [29][30][31]. Also, over the last years, the close relation between flat bands and compact localized states (CLSs) [32] was increasingly exploited [33][34][35][36][37][38][39]. A CLS is a wave function strictly localized to some finite region of the lattice, with zero probability amplitude outside this region.…”
Section: Introductionmentioning
confidence: 99%
“…So far, various tight-binding models with flat bands have been explored [14,[49][50][51][52][53][54][55][56][57][58], and many insights on the model construction have been accumulated. It was also found that some flat-band models have large sublattice degrees of freedom, resulting in multiple flat bands with different energies [59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%